Uloga rezultata za ciljanje atrijalne fibrilacije (STAF) u kombinaciji sa D-dimerom u skriningu ishemijskih pacijenata sa atrijalnom fibrilacijom: STAF and D-dimer for Screening AF in Ischemic Stroke - Liu, Libin; Xie, Peikai; Zhu, Peipei; Zhuo, Wenyan; Xu, Anding (Journal of Medical Biochemistry, 2023)
Background: We aim to explore the effect of the score for the targeting of atrial fibrillation (STAF) combined with the serum D-dimer (DD) level in screening acute ischemic stroke patients with atrial fibrillation (AF). Methods: This study is a retrospective case observation study. This study consecutively selected patients with acute ischemic stroke who were hospitalized in the Department of Neurology at Zhuhai Hospital Affiliated with Jinan University from February 2019 to February 2021. Venous blood was drawn from all patients within 24 hours of hospitalization for DD detection. In accordance with the medical records, the patients were classified into an AF group and a non-AF group and were scored according to the STAF standard. A combined test method was used to estimate the diagnostic screening value of the STAF combined with the DD value for acute ischemic stroke patients with AF. Results: A total of 480 patients were enrolled, of whom 73 patients (15.2%) had AF and 42 patients had paroxysmal AF. The diagnostic sensitivity of a STAF ≥ 5 for patients with AF was 78%, and the specificity was 91%. The diagnostic sensitivity of DD ≥ 826.5 ng/mL for AF was 70%, and the specificity was 76%. The diagnostic sensitivity of the two indicators combined for AF was 86%, and the specificity was 97%. Conclusion: The STAF combined with the serum DD level has good diagnostic value in screening acute ischemic stroke patients with AF.